DAMPAK AKTIFITAS EKONOMI BAWAH TANAH DAN KORUPSI TERHADAP TINGKAT PENDAPATAN, TINGKAT HARGA, DAN TINGKAT SUKU BUNGA DI INDONESIA (2010.Q1-2019.Q4) - ALOYSIUS HARI KRISTIANTO (Fakultas Ekonomi Universitas Prof. Dr. Hazairin, SH. Bengkulu, 2023)
To effectively decrease, regulate, and halt phenomena that are harmful to national revenue, special and constant attention must be paid to the phenomenon of underground economic activity, particularly in identifying the determination of this economic activity. The purpose of this research is to examine the effects of underground economic operations, the possibility for corruption, the evasion of tax payments, and the impact of economic activity on interest rates and the level of the stock market. The descriptive quantitative technique was utilized in conjunction with statistical test analysis and a classical assumption test to conduct the study. The findings of this study, which examines corruption at the national level, indicate that there is a positive relationship between corrupt behavior and underground economic activities, which are characterized by the money supply in a narrow sense (M1 - currency), and that increasing levels of corruption can lead to an increase in the money supply in a given society. Meanwhile, the greater the quantity of tax revenue collected, the greater the amount of money available for circulation (M1). To achieve this, there is a need to implement collaboration between government departments (good government), such as tax authorities, labor services, police, anti-corruption agencies and cooperatives and MSMEs, among others, and to begin implementing a digitalization system in every financial transaction by integrating it into the e-system of government (e-Government).